"Heidegger en Latinoamérica" (2006)
Heidegger has a huge reception in Latin America. Until now there was no academic work or dissertations about it, the first time that this theme is researched were on my dissertation: “The language by Heidegger und his oeuvre’s reception in Latin America”. The presence of Heidegger in this continent begins at late thirties in Mexico and Argentina. The first translation from his oeuvre “Sein und Zeit” was done and published in Mexico in 1951. The language by Heidegger is fundamental to understand his propose that is why the relation between Heidegger and Latin America was presented with the analysis from the language as the matrix of the reception. This work’s purpose was to demonstrate that in the field of the romance languages French is not the only one which has worked and enriched Heidegger’s propose but also in Spanish, in Latino American Spanish. With questions, which involved Heidegger and existentialismus, such as: Why they go back to Heidegger to aboard existential problems in Latin America? These existential items took to form the Hiperión group in Mexico and to reflect about the existentialimus by Heidegger in Argentina. The actual reception recognizes Heidegger as the father of post-modernisms and of the “post” in general. In the last period Heidegger is present in the entire continent but in this essay was specially studied the work done in Colombia and Argentina.